Validation of the 2017 European LeukemiaNet Classification for Acute Myeloid Leukemia With NPM1 and FLT3-Internal Tandem Duplication Genotypes - Boddu, Prajwal (Cancer, 2018)
BACKGROUND: The revised 2017 European LeukemiaNet (ELN) classification (ELN-2017) of acute myeloid leukemia (AML) divides patients into 3 prognostic risk categories, with additional factors such as the fms-like tyrosine kinase 3 (FLT3)-internal tandem duplication (ITD) allele ratio (AR) considered for risk stratification. To the best of the authors’ knowledge, the prognostic usefulness of ELN-2017 in comparison with ELN-2010 in younger patients with AML has not been validated to date. METHODS: The authors performed a retrospective study on patients aged <60 years who received idarubicin plus cytarabine (IA)-based induction chemotherapy for newly diagnosed AML. RESULTS: According to ELN-2017 criteria, the number of patients in the favorable (Fav), intermediate (Int), and adverse (Adv) risk categories was 192 patients (27%), 331 patients (46%), and 192 patients (27%), respectively. Overall survival probabilities at 5 years in the Fav, Int, and Adv groups were 57%, 37%, and 18%, respectively. In comparison, the 5-year overall survival probabilities in the Fav (169 patients), intermediate (IR)-1 (80 patients), IR-2 (306 patients), and Adv (160 patients) ELN-2010 categories were 59%, 32%, 40%, and 14%, respectively. Although ELN-2010 historically distinguishes prognosis into IR-1 and IR-2 categories in younger patients, this difference was nullified in the current study cohort. When comparing patients with a low FLT3-ITD AR with those with a high FLT3-ITD AR, no significant differences in survival were noted among patients with nucleophosmin 1 (NPM1)-mutated AML (P=.28) or wild-type NPM1 (P=.35), and in those treated with IA alone (P=.79) or those treated with IA and a FLT3 inhibitor (P=.10). CONCLUSIONS: The ELN-2017 more accurately distinguishes prognosis in patients with newly diagnosed AML. The lack of prognostic significance for the FLT3-ITD AR needs further evaluation in different treatment settings.